2022
DOI: 10.3389/fpubh.2022.951096
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of SARS-CoV-2 vaccine in hemodialysis patients: A systematic review and meta-analysis

Abstract: Rationale and objectiveCOVID-19 vaccination is the most effective way to prevent COVID-19. For chronic kidney disease patients on long-term dialysis, there is a lack of evidence on the pros and cons of COVID-19 vaccination. This study was conducted to investigate the immunogenicity and safety of COVID-19 vaccines in patients on dialysis.MethodsPubMed, MEDLINE, EMBASE, and the Cochrane Library were systemically searched for cohort, randomized controlled trials (RCTs), and cross-sectional studies. Data on immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The effectiveness of different vaccines against SARS-CoV-2 in patients receiving maintenance dialysis have been extensively studied previously, typically including BNT162b2 (P zer), mRNA-1273 (Moderna), ChAdOx1 nCoV-19 (AstraZeneca), and Ad26.COV2.S (Janssen) vaccines. Initial overall immunogenicity rate in dialysis patients reaches 87-89%, which is slightly lower than that of the general population [11,12]. However, vaccine-induced seroresponse seems to be waning over time across all vaccine types [13].…”
Section: Discussionmentioning
confidence: 92%
“…The effectiveness of different vaccines against SARS-CoV-2 in patients receiving maintenance dialysis have been extensively studied previously, typically including BNT162b2 (P zer), mRNA-1273 (Moderna), ChAdOx1 nCoV-19 (AstraZeneca), and Ad26.COV2.S (Janssen) vaccines. Initial overall immunogenicity rate in dialysis patients reaches 87-89%, which is slightly lower than that of the general population [11,12]. However, vaccine-induced seroresponse seems to be waning over time across all vaccine types [13].…”
Section: Discussionmentioning
confidence: 92%
“…In a previous study conducted in the ORCHESTRA cohort, we demonstrated that, at 9 months, antibody levels showed a decreasing trend over time without analyzing whether this was dependent on previous diseases or multimorbidity [ 18 ]. Several studies have investigated the humoral response to the SARS-CoV-2 vaccine in patients suffering from cancer, kidney failure, and immunosuppression, showing a lower immune response in these subjects [ 19 , 20 , 21 ]. Similar results were reported among subjects who underwent kidney transplant or who were affected by multiple sclerosis [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the humoral response to the SARS-CoV-2 vaccine in patients suffering from cancer, kidney failure, and immunosuppression, showing a lower immune response in these subjects [ 19 , 20 , 21 ]. Similar results were reported among subjects who underwent kidney transplant or who were affected by multiple sclerosis [ 19 , 20 , 21 , 22 ]. It is worth noting that there are likely many other factors that can influence the immune response to the virus and the vaccines, and more research is needed to fully understand this complex topic.…”
Section: Introductionmentioning
confidence: 99%
“…Although the prospect of sterile immunity has diminished considering novel variants, vaccinations are an effective measure against severe and fatal COVID-19 ( 13 ). There is now a large body of evidence displaying that SARS-CoV-2 vaccination elicits a dampened, but still measurable serological response in individuals on HD, who were excluded from initial trials ( 14 ). However, frequent booster shots may be necessary in this population to combat waning immunity and non-responders ( 15 ).…”
Section: Introductionmentioning
confidence: 99%